Fiscal independence and economic growth: A case study of Jember district in 2014-2023 - Ngesti, Begawan Damar (Educoretax, 2025)
This research aims to study and analyze 1). Growth in local taxes, local retribution, separated regional assets management result, other authorized local revenue, and gross regional domestic product in 2014-2023, 2). The influence of local taxes, local retribution, separated regional assets management result, other authorized local revenue on gross regional domestic product in 2014-2023. This research uses descriptive and quantitative analysis methods through secondary data on the realization of local taxes, local retribution, separated regional assets management result, other authorized local revenue, and gross regional domestic products. Testing of research variables using multiple regression analysis as a whole and partially. Result of research show that 1). Local tax, other authorized local revenue, and gross regional domestic product variables experienced an annual average increase of 11,205%, 11,50%., and 4,08% On the other hand, the variables of local retribution and separated regionall assets management result decreased by 2,44% and 0,35%. 2). Simultaneously, the variables of local taxes, local retribution, separated regional assets management result, other authorized local revenue have a significant effect on regional domestic product with an alpha significance level . While partially, only the local tax variable has a significant influence on gross regional domestic product on gross regional domestic products with an alpha significance level .